2003
DOI: 10.1093/jxb/erg128
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium‐responsive genes in sugarcane: identification and analysis of expression under oxidative stress

Abstract: Suppression subtractive hybridization (SSH) technology was used to gain preliminary insights into gene expression induced by the phytotoxic aluminium species, Al(3+), in sugarcane roots. Roots of hydroponically-grown Saccharum spp. hybrid cv. N19 were exposed to 221 microM Al(3+) at pH 4.1 for 24 h, a regime shown to inhibit root elongation by 43%, relative to unchallenged roots. Database comparisons revealed that, of a subset of 50 cDNAs ostensibly up-regulated by the metal in the root tips, 14 possessed puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 29 publications
3
54
1
2
Order By: Relevance
“…The transcripts of two different genes coding for tonoplast intrinsic proteins (TIPs) decreased under Al stress, which would suggest generation of a lower turgor pressure in the cell elongation zone resulting in reduced root growth (Milla et al, 2002). Watt (2003) indicated that 14 of the 50 cDNAs up-regulated by Al stress in sugarcane were involved in signalling events and the regulation of gene expression. Mao et al(2003) identified several Al-regulated genes related to the metabolism of cell wall components in rice.…”
Section: Genes or Proteins Regulated By Al Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…The transcripts of two different genes coding for tonoplast intrinsic proteins (TIPs) decreased under Al stress, which would suggest generation of a lower turgor pressure in the cell elongation zone resulting in reduced root growth (Milla et al, 2002). Watt (2003) indicated that 14 of the 50 cDNAs up-regulated by Al stress in sugarcane were involved in signalling events and the regulation of gene expression. Mao et al(2003) identified several Al-regulated genes related to the metabolism of cell wall components in rice.…”
Section: Genes or Proteins Regulated By Al Stressmentioning
confidence: 99%
“…However, most of these genes are general stress-inducible genes, whose expressions are turned on by oxidative stress (Ezaki et al, 1996;Richards et al, 1998;Watt, 2003), pathogen infection (Hamel et al, 1998;Cruz-Ortega et al, 1997;Watt, 2003), other metal ions (Snowden et al, 1995), and water-stress and cold stress (Watt, 2003). They are correlated with Al toxicity rather than tolerance to Al stress.…”
Section: Isolation and Cloning Of Genes For Al Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…SSH has successfully been used to identify genes responsive to various biotic and abiotic stresses in various plant species such as Saccharum (Watt 2003); Festuca (Zhang et al 2005); Pennisetum (Mishra et al 2007); Agrostis (Xu et al 2009); Triticum (Chauhan et al 2011). Thus in the current study we focus on identifying, validating and establishing the putative functions of the major differentially expressed genes in P. glaucum during drought stress response using SSH, real-time quantitative qRT-PCR and homology searches.…”
Section: Introductionmentioning
confidence: 99%
“…Since the parB and NtPox genes encode a glutathione S-transferase and a peroxidase, we also supposed that Al stress is probably linked to oxidative stress (Ezaki et al, 1996). Recently, Watt (2003) identified several Al stress-induced genes from Saccharum spp. hybrid cv N19, which are homologous to Ser/Thr kinase, RAS-related protein, GTPbinding protein, and so on.…”
mentioning
confidence: 97%